Unmaking the Arab/Muslim Child - Mansour, Nisrine (Middle East Journal of Culture and Communication, 2018)
Abstract Recent interest in Arab child audiences is mostly related to the penetration of digital media to the Arab region and the rise of discourses on ‘counterterrorism’, Islamic radicalization and Islamophobia. More often than not, audience-focused inquiry has adopted, as a starting point, the uniform default category of ‘Arab/Muslim’. As these analytical categories are conflated, the implications of such teleological epistemologies cannot be missed. In this article, I dislocate these ontological and epistemological assumptions about Arab child audiences by refocusing the inquiry on children’s own processes of meaning-making amid their negotiations of socioeconomic, political, migratory and media ecologies. This inquiry, conducted between 2013 and 2015, explores these spaces by zooming into the findings of ethnographic research and playful interventions with two Syrian and Palestinian children living in the two contrastive migratory settings of Beirut and London. This micro-analysis questions dominant understandings of Arab childhood and screen media use today, and discusses the potential for adopting a multifaceted approach to the inquiry.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2My8xODczOTg2NS0wMTEwMTAwNg